Comparative and Functional Analyses of Two Sequenced Paenibacillus polymyxa Genomes Provides Insights Into Their Potential Genes Related to Plant Growth-Promoting Features and Biocontrol Mechanisms - Li, Jin-Yi; Gao, Tan-Tan; Wang, Qi (Frontiers in Genetics, 2020)
Many bacteria belonging to Paenibacillus polymyxa are plant growth-promoting rhizobacteria (PGPR) with the potential to promote plant growth and suppress phytopathogens and have been used as biological control agents (BCAs). However, the growth promotion and biocontrol mechanisms of P. polymyxa have not been thoroughly elucidated thus far. In this investigation, the genome sequences of two P. polymyxa strains, ZF129 and ZF197, with broad anti-pathogen activities and potential for growth promotion were comparatively studied. Comparative and functional analyses of the two sequenced P. polymyxa genomes showed that the ZF129 genome consists of one 5,703,931 bp circular chromosome and two 79,020 bp and 37,602 bp plasmids, designated pAP1 and pAP2, respectively. The complete genome sequence of ZF197 consists of one 5,507,169 bp circular chromosome and one 32,065 bp plasmid, designated pAP197. Phylogenetic analysis revealed that ZF129 is highly similar to two P. polymyxa strains, HY96-2 and SQR-21, while ZF197 is highly similar to P. polymyxa strain J. The genes responsible for secondary metabolite synthesis, plant growth-promoting traits, and systemic resistance inducer production were compared between strains ZF129 and ZF197 as well as other P. polymyxa strains. The results indicated that the variation of the corresponding genes or gene clusters between strains ZF129 and ZF197 may lead to different antagonistic activities of their volatiles or cell-free supernatants against Fusarium oxysporum. This work indicates that plant growth promotion by P. polymyxa is largely mediated by phytohormone production, increased nutrient availability and biocontrol mechanisms. This study provides an in-depth understanding of the genome architecture of P. polymyxa, revealing great potential for the application of this bacterium in the fields of agriculture and horticulture as a PGPR.